PENGENALAN KOMPUTER KEPADA SISWA SDN 08 KEPAHIANG DENGAN MENGGUNAKAN APLIKASI KAHOOT - Aviantoro, Kevin; Eki Saputra, (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This activity aims to improve the effectiveness of digital computer science learning at SDN 08 Kepahiang using the Kahoot! application. The main problem faced is low student motivation and engagement in conventional teaching methods, which tend to be less interactive. This was achieved by implementing gamification through Kahoot! Gamification is a learning approach that uses game elements, such as points, challenges, and competitions, to increase student engagement, motivation, and understanding in the learning process. This approach aims to create a fun, competitive atmosphere. With real-time feedback provided by the application, teachers can adjust teaching methods based on direct student responses, making learning more adaptive and dynamic. The results of this activity indicate that Kahoot! not only increases student active participation but also improves their understanding of the computer science material. With this interactive approach, students are more motivated to engage in the learning process, significantly improving the quality of learning and learning outcomes.